The Public Sphere - Salvatore, A. author. aut Link
X, 293 p.
Keywords: This book explores conceptual and institutional developments of the notion of the public sphere in the West and in the Islamic world, tackling historic ruptures spanning the formation and transformation of the Euro-Mediterranean world. Set against an imploding grammar of socio-political life, the modern liberal public sphere appears in a new light.